Strategies to augment adherence in the management of sleep‐disordered breathing. Issue 4 (3rd July 2019) - Sunwoo, Bernie Y.; Light, Matthew; Malhotra, Atul
ABSTRACT: Continuous positive airway pressure (CPAP) is highly effective in treating sleep‐disordered breathing (SDB). However, unlike surgical interventions, this treatment modality relies heavily on patient acceptance and adherence. The current definition of adherence is largely arbitrary and is mainly used by third‐party payers to determine CPAP reimbursement but CPAP adherence remains sub‐optimal. Strategies to augment adherence, especially early in the course of a CPAP trial, are needed in the management of SDB. An understanding of the basis for observed differences in CPAP and oral appliance (OA) use is necessary in developing these strategies, but to date no single factor has been consistently identified. Consequently, a multidimensional approach using educational, behavioural, technological and potentially pharmacological strategies to target (i) disease characteristics, (ii) patient characteristics including psychosocial factors, (iii) treatment protocols and (iv) technological devices and side effects that may influence adherence, is likely required to augment the complex behaviour of CPAP and OA use. In the near future, we envision a personalized medicine approach to determine the risk of non‐adherence and set individualized adherence goals aimed at treating specific symptoms (e.g. excessive daytime sleepiness) and reducing the risk of patient‐specific SDB consequences (e.g. atherosclerosis). Resources for interventions to improve adherence such as educational programmes and telemedicine encounters could then be more efficiently allocated. Abstract : Find the whole series here